Unroofing and curettage for recurrent sacrococcygeal pilonidal disease - Koc, Mehmet Ali; Celasin, Haydar; Sunter, Kaan; Akyol, Cihangir; Gecim, Ibrahim Ethem (Frontiers in Surgery, 2024)
PurposeSacrococcygeal pilonidal disease (SPD) is a global concern, notably in Southeast Europe and the Middle East. Unroofing curettage (UC), which provides faster recovery, better cosmetic appearance, and lower recurrence rates in the primary cases, was evaluated with the results of recurrent disease.MethodsThis retrospective study included 74 patients with recurrent disease who were over 16 years of age, experienced recurrence after at least one surgical attempt, and underwent unroofing curettage between 2007 and 2019. Operation time, return to work duration, and recurrence rates were assessed.ResultsMean age of patients was 29.8 ± 10.6 years, and 61 (82.4%) were male. Previous procedures included excision + flap reconstruction, excision + primary closure, and local excision + lay open. Mean operation time for unroofing curettage was 22 ± 5.3 min. Mean durations for return to work and recovery were 5.9 ± 3 days, and 6.5 ± 2.6 weeks, respectively. Mean follow-up duration was 81.6 ± 49 months. Recurrence was only observed in 1 (1.3%) patient. Unroofing curettage showed a mean recurrence-free period of 156.9 months (95% CI [, 152.9–160.9 months).ConclusionUnroofing curettage stands out as a low-recurrence approach, likely to persist as a treatment method, especially for a selected group with recurrence.